2014
DOI: 10.1371/journal.pone.0104827
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Polymorphic ‘Switch’ That Influences miRNAs' Regulation of a Myasthenia Gravis Risk Pathway

Abstract: The significant roles of genetic variants in myasthenia gravis (MG) pathogenesis have been demonstrated in many studies, and recently it has been revealed that aberrant level/regulation of microRNAs (miRNAs) might contribute to the initiation and progression of MG. However, the dysfunction of miRNA associated with single nucleotide polymorphisms (miRSNPs) has not been well investigated in MG. In this study, we created a contemporary catalog of 89 MG risk genes via manual literature-mining. Based on this risk g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…4 A,B, seven pathways (PI3K-Akt signalling pathway and pathways in cancer, hepatitis B, bladder cancer, colorectal cancer, pancreatic cancer and prostate cancer) and two gene functions (positive regulation of cell proliferation and cytoplasm) were collectively enriched in both gene and miRNA analyses. Among these coenriched pathways, five were associated with cancer, and one was associated with infectious diseases, which is in accordance with our previous findings 15 17 .
Figure 4 Gene Ontology and KEGG pathway analysis using genes and targets of miRNAs in CFMSN.
…”
Section: Resultssupporting
confidence: 92%
“…4 A,B, seven pathways (PI3K-Akt signalling pathway and pathways in cancer, hepatitis B, bladder cancer, colorectal cancer, pancreatic cancer and prostate cancer) and two gene functions (positive regulation of cell proliferation and cytoplasm) were collectively enriched in both gene and miRNA analyses. Among these coenriched pathways, five were associated with cancer, and one was associated with infectious diseases, which is in accordance with our previous findings 15 17 .
Figure 4 Gene Ontology and KEGG pathway analysis using genes and targets of miRNAs in CFMSN.
…”
Section: Resultssupporting
confidence: 92%
“…Human MG risk gene data was acquired using the following two approaches: i) Gene information was obtained by searching certain current databases, including DisGeNET (http://www.disgenet. org/web/DisGeNET/menu) (15) and Online Mendelian Inheritance in Man (http://www.omim.org/) (16); and ii) using the protocols published in our previous studies (6,7), the gene was notably differentially expressed in more than five MG samples using dependable biological laboratorial techniques, and 9,514 items were browsed by manually collecting literature using the terms [myasthenia gravis (MeSH Terms) and English (Language)] and the species 'Homo sapiens' published prior to March 1st, 2017 on the PubMed database (https://www.ncbi. nlm.nih.gov/pubmed); the eligible genes were selected.…”
Section: Methodsmentioning
confidence: 99%
“…However, the majority of previous studies investigating MG risk genes have focused on only one or a few genes in cell lines without global analysis. Searches for a number of MG risk genes were performed in our previous studies (6,7), however, the risk genes identified previously were not sufficiently comprehensive. The global pathway analysis of MG risk genes in the present study may assist in further characterizing the pathogenesis of MG.…”
Section: Introductionmentioning
confidence: 99%
“…The species of the risk genes was limited to ' Homo sapiens '. We thoroughly read the 9,474 items returned by our searches and selected MG risk genes that met the following standards oulined in a previous study ( 16 ): i) the gene was presented in at least 5 MG samples (including blood samples and thymic tissue samples); ii) the gene was detected using reliable experimental methods, such as microarrays and RT-PCR; and iii) the gene was significantly differentially expressed (mRNA level or protein level). In addition, we also collected MG risk genes from current public databases, including the Genetic Association Database (GAD) ( 17 ), DisGeNET ( 18 ), Online Mendelian Inheritance in Man (OMIM) ( 19 ) and Functional Disease Ontology Annotation (FunDO) ( 20 ).…”
Section: Methodsmentioning
confidence: 99%